In defense of politicization of human rights : the UN special procedures - Domínguez Redondo, Elvira (New York : Oxford University Press, 2020)
"International human rights have been largely understood and articulated as limitations to state sovereignty, leading to the widely shared view that only expert- driven non- politicized work can ultimately hold states accountable for not upholding them. This approach has had significant success but comes up against the boundaries of states' political will and actual influence in implementing human rights. The creation of the Human Rights Council, intensifying states' prominence within the system, especially through the establishment of the Universal Periodic Review, was an advance met with initial resistance by academic and practitioner communities. This book questions the blunt critique of "politicization" as not nuanced enough to understand progress, through the lenses of the Special Procedures of the Human Rights Council. These mechanisms are ideally located in the system to analyze the impact of politicization on the international human rights system. Depending on a political decision to be established and renewed, they are particularly sensitive to political factors. However, they are also held by independent experts. The scope of thematic mandates is universal preventing the application of bias associated with politically driven processes"--
Introduction : testing the impact of politicization on human rights -- Creation, institutionalization, and development of public and confidential special procedures -- The politics of reforming special procedures -- Growing organically : a "system" of special procedures -- Shuttling between diplomacy and expertise in developing methods of work -- Implementation of methods of work -- Politics of "independence" : Position of special procedures within the United Nations.
Includes bibliographical references (page : [199] - 215) and index.
Keywords: United Nations Human Rights Council; International law and human rights; Human rights -- Political aspects